Adversity Quotient, Komitmen Organisasi dan Kesiapan Untuk Berubah Dalam Meningkatan Kinerja Karyawan Di Masa Pandemi Covid-19 - Harry Theozard Fikri; Rika Wahyuni; Isna Asyri Syahrina; Frihapma Semita Ade; Rina Mariana (JURNAL PSIKOLOGI, 2021)
Optimizing employee performance is meaningful and must be tried in an effort so that businesses can always survive the situation Covid-19 pandemic. If employees have high performance, their participation in the running of a business tends to be high. The purpose of this study was to examine and determine the effect of adversity quotient, organizational commitment and readiness to change on supermarkets employees performance in Padang City. There are 108 supermarkets employees in Padang city with purposive sampling method. The research data were collected using a questionnaire adversity quotient, organizational commitment, readiness to change and employee performance. The results of empirical research prove accepted and proven. There was a positive influence between adversity quotient on employee performance H1 is accepted. There is a positive influence between organizational organizations on employee performance H2 is accepted. The results of the third study proved that there is a positive influence between readiness to change on employee performance H3 is accepted. Data were analyzed using Multiple Linear Regression with IBM SPSS Statistics 23 for Windows. From the results, it is proven that the optimization of employee performance during the Covid-19 pandemic done through an adversity quotient, organizational commitment and employee readiness to change.